2012
DOI: 10.1108/14601061211272376
|View full text |Cite
|
Sign up to set email alerts
|

Intermediaries driving eco‐innovation in SMEs: a qualitative investigation

Abstract: The purpose of this paper is to identify the role intermediaries can play in an SME's pursuit for corporate sustainability with a focus on eco-efficiency innovation. The research identifies drivers and barriers for eco-efficiency innovation, and highlights effects induced through collaboration between SMEs and local authorities, on the one hand, and consultancies, on the other. Design/methodology/approach: This paper is based on an exploratory qualitative interview study among German SMEs of the metal and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 74 publications
(123 reference statements)
5
128
0
6
Order By: Relevance
“…At the same time, the literature on drivers also reports some evidence about the supportive role of intermediary organisations in advancing sustainable entrepreneurship in SMEs (e.g. Klewitz et al, 2012).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the literature on drivers also reports some evidence about the supportive role of intermediary organisations in advancing sustainable entrepreneurship in SMEs (e.g. Klewitz et al, 2012).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…They have made them realise that by becoming environmentally responsible they could simultaneously protect the wider natural environmental, serve environmentally sensitive customers, comply with regulations and achieve eco-efficiency (Ortolano et al, 2014;Van Berkel, 2007). While such an active role of intermediary organisations in transforming environmental behaviour of firms has been observed in some European countries (Bruijn and Lulofs, 2001;Klewitz et al, 2012;Pimenova and van der Vorst, 2004;York and Venkataraman, 2010), these organisations have been financially supported by national governments, highlighting the effectiveness of strong institutional structures in these economies. In contrast, the CPCs in Pakistan have not been financially backed by national government, but by international sponsors (Ortolano et al, 2014).…”
mentioning
confidence: 99%
“…Furthermore, according to Shrivastava (1995) environmental technologies help companies to establish a social presence on markets where they operate, gain social legitimacy and maintain good public relations and corporate image. Improved firm reputation through the implementation of sustainable practices is an important driver for corporate businesses (Pellegrini-Masini and Leishman 2011; Klewitz et al 2012); in particular, green product development seems to be driven by improvement of reputation and corporate image (Dangelico and Pujari 2010). Based on a sample of Italian companies, image improvement was found in 80% of companies to be the strongest stimulus for the introduction of environmental management systems (ISO 14001) (Salomone 2008).…”
Section: Expected Benefits From Eco-innovationmentioning
confidence: 99%
“…Companies also start to deploy eco-innovation in order to pursue benefits derived from its implementation, including cost savings (Horbach 2008;Belin et al 2011;Demirel and Kesidou 2011;Horbach et al 2012;Klewitz et al 2012;Triguero et al 2013;Chassagnon and Haned 2014) and improvement of firm reputation (Agan et al 2013;Chen 2013;Sarkar 2013). Shrivastava (1995) summarized a few other benefits deriving from successful eco-innovation implementation: improved relationships with local communities, access to new green markets and gain of competitive advantage.…”
Section: Expected Benefits From Eco-innovationmentioning
confidence: 99%
“…Eco-innovation and better environmental performance can lead to the reduction of several expenditures, especially in the following areas: cost of materials, energy and services; cost of capital; cost of labor; risk management and relations with external stakeholders [Ambec, Lanoie, 2008]. Based on a study of SMEs, Klewitz [Klewitz, 2012] found that companies can benefit from cost savings (increased energy efficiency) when dealing with sustainability-related issues. Large financial gains can thus be derived from energy and material saving, waste reduction, and addressing lifecycle costs [Shrivastava, 1995].…”
Section: Hypothesismentioning
confidence: 99%